2008
DOI: 10.1542/peds.2007-1365
|View full text |Cite
|
Sign up to set email alerts
|

A Policy-Based School Intervention to Prevent Overweight and Obesity

Abstract: A multicomponent school-based intervention can be effective in preventing the development of overweight among children in grades 4 through 6 in urban public schools with a high proportion of children eligible for free and reduced-priced school meals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
393
6
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(425 citation statements)
references
References 21 publications
13
393
6
13
Order By: Relevance
“…6,21 Many studies spanned age groups, including infancy through the preschool ages, 22,29 preschool through school age, 17,25,26,27,30 and school age through adolescence. 6,10,[18][19][20]26,32 Many studies were based on secondary analysis of datasets, including the Pediatric Nutrition Surveillance System (PedNSS; n = 3); National Longitudinal Survey of Youth (NLSY; n = 2), Cambridge Public School Health Surveillance System (n = 2); or others (n = 3). Nine studies analyzed primary data, including five intervention studies randomized at the school level and providing control arm data.…”
Section: Literature Overviewmentioning
confidence: 99%
“…6,21 Many studies spanned age groups, including infancy through the preschool ages, 22,29 preschool through school age, 17,25,26,27,30 and school age through adolescence. 6,10,[18][19][20]26,32 Many studies were based on secondary analysis of datasets, including the Pediatric Nutrition Surveillance System (PedNSS; n = 3); National Longitudinal Survey of Youth (NLSY; n = 2), Cambridge Public School Health Surveillance System (n = 2); or others (n = 3). Nine studies analyzed primary data, including five intervention studies randomized at the school level and providing control arm data.…”
Section: Literature Overviewmentioning
confidence: 99%
“…In contrast, Epstein et al 18 found that with an intervention targeting only television viewing and computer use over a 2-year period, change in BMI z-score was significant only in children from families of low SES. Similarly, Foster et al 26 showed that a multicomponent school-based intervention for 2 years involving older children (mean age 11 years) from low SES, resulted in marked reduction in the prevalence of overweight; odds ratios and 95% confidence interval were 0.65 (0.54-0.79).…”
Section: Discussionmentioning
confidence: 94%
“…The majority of prevention programs promoted physical acti vity 4,9,[11][12]14,16,24,[26][27][28][29]38,40,46,50,51,53 and two programs recommended physical activity. 15,55 All the studies included programs that encouraged healthy dietary habits through presentations and didactic materials.…”
Section: Resultsmentioning
confidence: 99%
“…2 When analyzed individually, the studies included in this review demonstrated positive results from lifestyle changes that reduced television, videogame and computer screentime, [14][15]50 that increased the consumption of fruits and vegetables [14][15] and that reduced the consumption of foods rich in fat. 4,14 These fi ndings reinforce the importance of developing actions and programs to change lifestyles among this age group, since their lifestyles are in formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation